Islamic Law and Positive Law in Indonesia’s Transgender Behavior - Radatilla; Aisyah, Siti (Mazahibuna: Jurnal Perbandingan Mazhab, 2021)
Transgender Issues in Islamic Law and Positive Law are the focus of this article. A multidisciplinary technique, specifically a normative-juridical approach, is used to address these questions and analyze descriptive data. This study is classified information. Analyzing representative literature and making sure its content is relevant to the issues being debated are all part of the process of conducting this form of library research. Researchers concluded that transgender is the transfer of behavior between men and women that is socially manufactured, essential differences between men and women that are not natural or decided by Allah SWT, but rather the result of the actions of both men and women themselves. It's still up for dispute whether or not there are transgender people in Indonesia. They can do whatever they want as long as the organization accepts that transgender individuals have the same human rights as everyone else. Changing one's gender is not a mental illness. Transgender people, on the other hand, are particularly vulnerable to mental health issues brought on by internal struggle and external pressure